Paenibacillus kribbensis AM49로 발효시킨 택사의 항산화 활성 및 NO 생성 효과 - 유동진; Dong-jin Yoo; 김창은; Chang-eun Kim; 유수정; Soo-jung Yoo; 전문희; Moon-hee Jeon; 김수현; Soo-hyun Kim (大韓本草學會誌, 2021)
Objectives : The purpose of this study was to investigate the antioxidant activities and nitric oxide (NO) production in RAW 264.7 macrophages in extract of Alisma orientale Juzep (EAOJ) and fermented extract (FAOJ) by Paenibacillus kribbensis AM49 (P. kribbensis AM49). Methods : The Alisma orientale Juzep was fermented with P. kribbensis AM49 at 37℃ for 72 hours. We measured total polyphenol and total flavonoid, DPPH radical scavenging activity, FRAP activity and reducing power by spectrometric assay in EAOJ and FAOJ at concentrations at 0.5, 1, 5, 10 ㎎/㎖. Positive control was used ascorbic acid. Furthermore, we examined effect of EAOJ and FAOJ on the cell viability and NO production in RAW 264.7 macrophages. Results : The total polyphenol and total flavonoids content of FAOJ were increased 9.16 ㎎/g, 2.59 ㎎/g to 12.58 ㎎/g, 3.45 ㎎/g. DPPH radical scavenging activity, FRAP activity and reducing power were dose dependently increased according to the treatment concentration (0.5, 1, 5, 10 ㎎/㎖) of EAOJ and FAOJ. In particular, DPPH radical scavenging activity, FRAP activity of FAOJ was significantly increased at 5, 10 ㎎/㎖. Reducing power of FAOJ at 10 ㎎/㎖ was similar to ascorbic acid at 0.1 ㎎/㎖. In addition, the cell viability and NO production in RAW 264.7 macrophages were significantly increased at the concentrations of 250, 500, 1000 ㎍/㎖. Conclusions : These results suggest that FAOJ by P. kribbensis AM49 has effects to antioxidant activity. In addition, the cell viability and NO production in RAW 264.7 macrophages were significantly increased.